Decreased retinal nerve fibre layer thickness detected by optical coherence tomography in patients with ethambutol‐induced optic neuropathy - Chai, Samantha J (BMJ Group, 2007)
BACKGROUND: It is difficult to assess the degree of optic nerve damage in patients with ethambutol‐induced optic neuropathy, especially just after the onset of visual loss, when the optic disc typically looks normal. AIM: To evaluate changes in retinal nerve fibre layer thickness (RNFLT) using optical coherence tomography (OCT) in patients with optic neuropathy within 3 months of cessation of ethambutol treatment. DESIGN: A retrospective observational case series from a single neuro‐ophthalmology practice. METHODS: 8 patients with a history of ethambutol‐induced optic neuropathy were examined within 3 months after stopping ethambutol treatment. All patients underwent a neuro‐ophthalmologic examination, including visual acuity, colour vision, visual fields and funduscopy. OCT was performed on both eyes of each patient using the retinal nerve fibre layer analysis protocol. RESULTS: The interval between cessation of ethambutol treatment and the initial visit ranged from 1 week to 3 months. All patients had visual deficits characteristic of ethambutol‐induced optic neuropathy at their initial visit, and the follow‐up examination was performed within 12 months. Compared with the initial RNFLT, there was a statistically significant decrease in the mean RNFLT of the temporal, superior and nasal quadrants (p = 0.009, 0.019 and 0.025, respectively), with the greatest decrease in the temporal quadrant (mean decrease 26.5 μm). CONCLUSIONS: A decrease in RNFLT is observed in all quadrants in patients with ethambutol‐induced optic neuropathy who have recently discontinued the medication. This decrease is most pronounced in the temporal quadrant of the optic disc.